Religious-Based Women’s Organization : Da’wah Movenment through Twitter Social Media - Ditha Aditya Pernikasari; Budi Dwi Arifianto; Junaedi, Fajar (Jogjakarta Communication Conference (JCC), 2023)
This study aims to explain the 'Aisyiyah proselytizing movement using twitter. This research is descriptive with the paradigm of postpositvism. This study used QDAS (Qualitive Data Analysis Software) Nvivo 12 Plus in analyzing data using the Chart analysis and Word Frequency features. The source of data in this study is the social media account twitter @PP'Aisyiyah. The results showed that ' Aisyiyah as a religious-based women's organization was able to adapt in carrying out its proselytizing from contemporary to digital massively through @PPAisyiyah's twitter account. Dakwah 'Aisyiyah on twitter is more dominant on the content of the convey of the hadith. Meanwhile, Aisyiyah's proselytizing narrative on twitter focuses on the women's movement adapting to the current situation. Then the intensity of proselytizing on twitter 'Aisyiyah was highest in April to June along with the direction from the Leader of 'Aisyiyah to continue preaching in the conditions of Covid-19. More than that, the chords involved with 'Aisyiyah in proselytizing on twitter are academic figures and Muhammadiyah figures.